2023
DOI: 10.3390/galaxies11010036
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in Finding Binary Systems with the B[e] Phenomenon

Abstract: This paper describes recent studies of the FS CMa-type objects, a group of stars showing the B[e] phenomenon defined in 2007. The objects exhibit strong emission-line spectra with both permitted and forbidden lines suggesting the presence of a B-type star as well as strong IR excesses due to radiation of circumstellar dust. These properties are hard to explain in the framework of the evolution of single stars with luminosities between ~300 and ~30,000 L⊙ typical of most B-type stars. We explore the hypothesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 79 publications
0
1
0
Order By: Relevance
“…However, only a few objects of this class have been confirmed as binary systems, probably due to the scarcity of available observational data to discover them and the difficulties in detecting signs of binarity due to the presence of CS matter, the intrinsic stellar variability, and the low brightness of most members of the FS CMa group [10]. Recently, Miroshnichenko et al [11] published a review of FS CMa objects, where they reported fifteen stars as binaries and six as binary system candidates.…”
Section: Introductionmentioning
confidence: 99%
“…However, only a few objects of this class have been confirmed as binary systems, probably due to the scarcity of available observational data to discover them and the difficulties in detecting signs of binarity due to the presence of CS matter, the intrinsic stellar variability, and the low brightness of most members of the FS CMa group [10]. Recently, Miroshnichenko et al [11] published a review of FS CMa objects, where they reported fifteen stars as binaries and six as binary system candidates.…”
Section: Introductionmentioning
confidence: 99%